A review on the biocompatibility and potential applications of graphene in inducing cell differentiation and tissue regeneration. Issue 17 (24th March 2017) - Wu, Xiaowei; Ding, Shinn-Jyh; Lin, Kaili; Su, Jiansheng
Abstract : Advances in the biocompatibility and cell differentiation inducing capacity of graphene and its potential applications in multi-tissue regeneration. Abstract : Tissue defects are usually caused by trauma, tumors, deformity, and infection. Use of tissue engineering technology to regenerate the defects, especially based on stem cells, has attracted widespread attention in recent years. To achieve faster healing and reconstruction of large scale defects, it is critically important to find scaffolds that are best for attachment and proliferation and can even induce the differentiation of stem cells. Recently, graphene and its derivatives have drawn significant attention due to their special physical and chemical properties, especially their biological properties. In this review, we summarized recent advances in tissue engineering based on graphene-family nanomaterials. For this purpose, a general description was provided to elucidate the biocompatibility, stimulation effects of graphene on cell differentiation, their potential applications in tissue regenerations, and the biodegradation property of the graphene-based materials. Moreover, the limitations and future trends of the applications of graphene in the biomedical field have been presented.